Determinants of pneumococcal carriage by age in Africa (2000–2021): a systematic analysis - Kwesi-Maliepaard, Eliza Mari; Opoku, Nicholas Kwasi-Do Ohene; Egyir, Beverly; Dayie, Nicholas TKD; Kusi, Kwadwo Asamoah; Frimpong, Augustina (Frontiers in Medicine, 2025)
BackgroundStreptococcuspneumoniae (S. pneumoniae) is one of the major pathogenic bacteria involved in pneumonia, with pneumococcal pneumonia often preceded by nasopharyngeal carriage of S. pneumoniae. The burden of pneumococcal pneumonia is highest in low-and middle-income countries, particularly in Africa. This systematic review examined the determinants of pneumococcal carriage across different age groups in Africa by analysing studies conducted between 2000 and 2021.MethodsOur search strategy and inclusion criteria focused on studies describing pneumococcal carriage in Africa, from which we extracted data on group size, pneumococcal carriage, identification methods, vaccination status, respiratory tract infections, and underlying diseases.ResultsOur findings indicate the highest pneumococcal carriage rates in children under 5 years, while data on carriage in the elderly (60 years and above) remains limited. HIV/AIDS, as an underlying disease, was associated with increased pneumococcal carriage. Carriage of serotypes included in the pneumococcal vaccines was decreased in those vaccinated compared to non-vaccinated. However, we did not observe an effect of pneumococcal vaccination on total carriage, suggesting replacement of vaccine-type serotypes by non-vaccine serotypes.DiscussionThis indicates the need for further research to understand the impact of pneumococcal vaccination among all age groups in diverse geographical locations. Special emphasis should be given to the elderly population, since they are understudied and have a higher burden of infectious diseases in general. This review provides an overview of pneumococcal carriage in all age groups in Africa, identifying key determinants of carriage and emphasizing the need for targeted interventions to reduce pneumococcal carriage in high-risk populations. Future research should investigate factors contributing to the observed vaccination-carriage relationship and explore strategies to enhance the effectiveness of pneumococcal vaccination programs in Africa.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42021274041.